Examining the Factors that Affected on Foreigner Tourists’ Satisfaction Travelling to Beach in Phuket - Soonsan, Nimit; Somkai, Umaporn (KKBS Journal of Business Administration and Accountancy, 2020)
This study investigates whether satisfaction can influence overall experience toward the beach destination in Phuket. The 400 foreign tourists were surveyed satisfaction and experience with questionnaire from beaches in Phuket. The convenience sampling technique was used to collect the data. The results of a regression analysis indicate that satisfaction toward the beach characteristics and satisfaction toward the safety influence the tourists’ overall experience. However, satisfaction toward the sea characteristic do not significantly influence their overall experience. Suggestions for future studies in the region and possible implications are discussed.